Customary Council Decisions as Grounds for the Elimination of Prosecution: Notes on the Criminal Procedure Code - Aris Hardinanto; Zico Junius Fernando; Nahdiya Sabrina; Eka Nugraha Putra; Benny Sumardiana (Universitas Negeri Semarang, 2026)
This article examines whether decisions issued by customary councils should constitute a legal ground for the elimination of prosecution under Indonesia’s Law No. 20 of 2025 on the Criminal Procedure Code. Following the enactment of Law No. 1 of 2023 on the National Criminal Code, customary criminal law has been formally recognized as part of Indonesian living law. However, the Criminal Procedure Code does not provide procedural provisions governing the relationship between customary justice mechanisms and the state criminal justice system. Using normative legal research with statutory and case approaches, this study analyzes Supreme Court jurisprudence recognizing customary decisions as a valid basis for eliminating prosecution. The findings indicate that the lack of procedural recognition creates legal uncertainty and undermines the principle of legal pluralism. Therefore, this article proposes the inclusion of a specific provision in the Criminal Procedure Code that recognizes customary council decisions as a ground for eliminating prosecution when the offender has complied with the imposed customary sanction.